Evaluasi Efektivitas Sistem Informasi Manajemen Pendidikan Dalam Meningkatkan Pengelolaan Data Siswa Dan Proses Pembelajaran Di Sekolah Menengah Atas Sukma Bangsa Lhokseumawe - Prayoga, M. Aditya; Poncowati, Srikandi Dwi; Ishaac, Muhamad (Jurnal Manajemen Pendidikan : Jurnal Ilmiah Administrasi, Manajemen dan Kepemimpinan Pendidikan, 2023)
The purpose of this study is to examine the extent to which the Education Management Information System (SIM Pendidikan) plays a role in improving student data management and the teaching-learning process at Sukma Bangsa High School in Lhokseumawe. In this study, qualitative methods were applied and data were collected through observation techniques and interviews with relevant resource persons. From the results of the study, it was revealed that the Education Management Information System (SIM Pendidikan), which includes SISTO and SIMAKA, has successfully integrated student data and curriculum management effectively. Although it is efficient in information management, challenges such as network limitations are still faced. However, planned evaluation efforts by the pusdatin team and system improvement plans have been identified to overcome these obstacles. Thus, SIM Pendidikan proved to make a valuable contribution in improving the effectiveness of student data management and learning processes at Sukma Bangsa Lhokseumawe High School. The results also highlighted the success of the Education SIM in improving parental engagement through online access to monitor the progress of their children's grades. Nonetheless, some technical constraints such as power outages or server problems are still a challenge, although pusdatin is actively addressing them. Planned evaluations by the pusdatin team are expected to improve the Education SIM by adding new features and making improvements based on the evaluation results. Although this process may be time-consuming, the system has proven to make a valuable contribution to teachers and school staff in completing their tasks more efficiently. The results of this study illustrate the importance of an Education SIM in an educational context.